Kinetics of Ammonium Thiosulfate Wet Air Oxidation under High‐Temperature Conditions. Issue 9 (29th July 2022) - Wurm, Julian; Pöschmann, René; Thielert, Holger; von Morstein, Olaf; Repke, Jens-Uwe
Abstract: To remove H2 S and HCN from acid gases, wet‐oxidative desulfurization such as the Takahax process can be applied. There, a continuous wastewater stream with high concentrations of ammonium thiosulfate and thiocyanate is discharged. By wet air oxidation of these salts at 473–573 K, fertilizer‐grade ammonium sulfate can be obtained. Thiosulfate wet air oxidation kinetics was investigated under industrially relevant conditions via the oxygen consumption rate in a high‐pressure reactor. Kinetic parameters were estimated with a dynamic reactor model. The experimental data was reproduced with a good average deviation of 2.17 %, and the applied reaction pathway is simple due to the high temperatures. This is an important step towards taylor‐made reactors for wet air oxidation of Takahax wastewater. Abstract : The Hirohax process offers an efficient way to deal with Takahax desulfurization wastewater by wet air oxidation of ammonium thiosulfate to fertilizer‐grade ammonium sulfate. The reaction kinetics was determined at varying temperatures, pressures, and thiosulfate concentrations. The estimated parameters can be applied for the development of optimal reactors for wet air oxidation of such wastewater.